DIALECTICAL UNITY OF LANGUAGE AND SPEECH (ON THE MATERIAL OF WORDS ENDING ON THE SUFFIX -LY IN ENGLISH LANGUAGE) - Kemertelidze, Nino (European Scientific Journal, ESJ, 2014)
In English language adjectives do not have completely expressed morphological indicators while adverbs have a complex morphological structure; otherwise saying, in qualitative adverbs the stem of attributive adjectives is complicated with the suffix -ly. The relation between adjectives and adverbs is quite often realized in word formation. In this case a word with the suffix -ly is considered as an adverb derived from a qualitative adverb with the help of the rather productive suffix. The fact that adjectives have the corresponding words ending on the suffix -ly indicates that we deal with such derived words which have already been established in the language and have lexicographically been fixed as linguistic units. Analysis of the material on language and speech levels showed that in English language there are words ending on the suffix -ly which are already derived from adjectives, are fixed in the dictionary and develop their meanings. On the other hand, these are those adjectives that do not have fixed parallel forms with -ly suffix, but there is the inexhaustible possibility of formation such words in speech. Being widely used in speech, such formations on their turn can be placed in dictionaries. Thus, vector of direction in this case can go not from language to speech as it mostly happens, but from speech to language. This fact once more proves dialectical unity of language and speech, that though being different phenomena, they are inseparable.